1999
DOI: 10.1046/j.1365-2125.1999.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic‐pharmacodynamic profile of systemic nitric oxide‐synthase inhibition with L‐NMMA in humans

Abstract: Aims It has been demonstrated that inhibition of endothelium derived nitric oxide with N G -monomethyl-l-arginine (l-NMMA) results in a different cardiac and peripheral vascular response. The purpose of this study was to investigate the pharmacokinetic-pharmacodynamic profile of l-NMMA and pharmacokinetic interactions with l-arginine in healthy subjects. Methods Plasma pharmacokinetics were analysed from two different studies: In study 1, 3 mg kg −1 l-NMMA was administered i.v. over 5 min and systemic haemodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 27 publications
4
52
0
Order By: Relevance
“…A role of increased NO synthesis, release of NO, or altered NO sensitivity by training is also supported by our results obtained in the ocular vasculature. NO is an important regulator of ocular blood flow, and the choroidal vasculature is particularly sensitive to changes in NO production (31). We have previously demonstrated that the ocular responsiveness to L-NMMA is reduced in patients with long-standing type 1 diabetes (12), which is compatible with the results of the present study.…”
Section: Fuchsjä Ger-mayrl and Associatessupporting
confidence: 82%
“…A role of increased NO synthesis, release of NO, or altered NO sensitivity by training is also supported by our results obtained in the ocular vasculature. NO is an important regulator of ocular blood flow, and the choroidal vasculature is particularly sensitive to changes in NO production (31). We have previously demonstrated that the ocular responsiveness to L-NMMA is reduced in patients with long-standing type 1 diabetes (12), which is compatible with the results of the present study.…”
Section: Fuchsjä Ger-mayrl and Associatessupporting
confidence: 82%
“…L-NMMA is cleared predominantly by hepatic amino acid pathways, with a minor amount of renal clearance at higher doses (31). In healthy adults, the mean elimination half-life of a 3 mg/kg L-NMMA dose is about 1 hour (26,32). In contrast, septic adults have a longer elimination half-life (2-3 hours) (31).…”
Section: Discussionmentioning
confidence: 99%
“…Saline or L-NMMA (1 ml) was continuously injected for 30 min via the right femoral vein, starting from myocardial ischemia until reperfusion. All rats were further injected intraperitoneally (ip) with L-NMMA or saline every 12 h for a period of 48 h. 39 …”
Section: Animals and Mirmentioning
confidence: 99%